Domain-driven design with Java : a practitioner's guide : apply DDD to create easy, elegant, and inventive software solutions for complex business problems /: a practitioner's guide : apply DDD to create easy, elegant, and inventive software solutions for complex business problems. (2022) - Chandrasekaran, Premanand; Krishnan, Karthik
No abstract available